PRE-TRIAL DETENTION OF TERRORISM SUSPECTS: THE APPLICATION OF THE EUROPEAN CONVENTION ON HUMAN RIGHTS - Guimarães, Bruno de Brito; Corrêa, Luna Tainara dos Santos (Revista do CEPEJ, 2017)
The present article makes a reflection about the violations of human rights in detentions of suspects of terrorism prior the trial. The works focuses on the system of human rights in Europe and the applicability of the European Convention on Human Rights provisions. In this line, first it will be understood the concept of terrorism to the European law and what are the situations in which an individual can be detained. After, we will quickly approach the definition of pre-trial detention and its applicability in cases involving terrorism acts. After the definition of terrorism and pre-trial detention concepts, how the protection of human rights is executed in Europe will be explained, focusing on the European Convention on Human Rights and in the fundamental role of the European Court of Human Rights in identifying violations of the Convention provisions. Following, it will be featured the rights contained in the Convention applicable to detainees, those being the prohibition of torture and the right to liberty and personal security. Thus, it will be outlined jurisprudence of the Court which deals with violations of these rights in cases of terrorism. Finally, it will be exposed the need to respect the fundamental precepts even in situations of insecurity and threat to national peace of European states.